Comparative Study of Stock, Mutual Fund, and Cryptocurrency Investments - Annisa Permatasari; Wahyudi Widodo (Enigma Institute, 2023)
Within the realm of investment, investors are presented with a multitude of options in terms of investment vehicles. Three options that are experiencing growing popularity include equities, collective investment schemes, and digital currencies. The literature search was conducted across multiple databases, including PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to explore the comparative aspects of stock investments, mutual funds, and cryptocurrencies. Stocks are a type of investment that symbolize ownership in a corporation, offering the possibility of long-term earnings through the firm's expansion and delivery of dividends. Stocks exhibit diverse levels of risk contingent upon the specific firm and industry and are typically more suitable for investors with long-term objectives. Mutual funds are financial instruments that aggregate capital from multiple investors and allocate it into a diversified collection of investments. This service offers automated diversification and is ideal for investors seeking to entrust the management of their portfolio to professionals. Mutual funds are appropriate for both short-term and long-term objectives. Cryptocurrencies are virtual assets that are bought and sold on cryptocurrency exchanges. Cryptocurrencies exhibit a high degree of speculation and volatility, characterized by swift and unpredictable price movements. Investing in cryptocurrencies necessitates a comprehensive comprehension of technical aspects and entails substantial risks, typically regarded as a short-term or speculative investment.